Stromal Tumor-infiltrating Lymphocytes in NRG Oncology/NSABP B-31 Adjuvant Trial for Early-Stage HER2-Positive Breast Cancer. (19th March 2019) - Kim, Rim S; Song, Nan; Gavin, Patrick G; Salgado, Roberto; Bandos, Hanna; Kos, Zuzana; Floris, Giuseppe; Eynden, Gert G G M Van den; Badve, Sunil; Demaria, Sandra; Rastogi, Priya; Fehrenbacher, Louis; et al.
Abstract: We retrospectively assessed association of stromal tumor-infiltrating lymphocytes (sTILs) with clinical outcomes and molecular variables reportedly predictive of trastuzumab-benefit in National Surgical Adjuvant Breast and Bowel Project B-31 (N = 2130). sTILs were assessed in 1581 eligible B-31 cases utilizing all available hematoxylin and eosin slides. Mean concordance between main reviewer and six other pathologists was 90.8% in 100 cases. Cox regressions were used to calculate hazard ratios (HRs). In chemotherapy and trastuzumab added to chemotherapy arms, increases in sTILs, as a semicontinuous variable (combined arms HR = 0.42, 95% confidence interval = 0.27 to 0.64, two-sided P  < .001) or as lymphocyte-predominant breast cancer with more than 50% sTILs (combined arms HR = 0.65, 95% confidence interval = 0.49 to 0.86, two-sided P  = .003) were statistically significantly associated with improved disease-free survival. There was no association of sTILs with trastuzumab benefit. However, higher sTILs were statistically significantly associated with higher trastuzumab benefit groups by 8-gene prediction model (two-sided P  < .001). Neither PIK3CA mutations nor Fc-gamma-receptor polymorphisms were associated with sTILs. sTILs may have utility as a prognostic biomarker identifying HER2-positive early breast cancer at low recurrence risk.